Effect of Different Pollinator Attractant Crops for Seed Setting and Maximizing Seed Yield of Onion - Uddin, Md. Kalim; Kamal, M. M.; Akand, M. M.; Hasan, M. M.; Chowdhury, M. N. A. (International Journal of Applied Sciences and Biotechnology, 2015)
The experiment was conducted at the Spices Research Centre, Shibgonj, Bogra during rabi season, 2010-11and 2011-12 to identify the suitable pollinator attractant crops for increasing the vigilance of pollinators and higher seed settings and thereby increasing seed yield of onion. In 2010-11, the highest seed setting was recorded in onion + fennel (69.88%) which was statistically identical to Onion + coriander (67.45 %) and Onion + black cumin (64.15 %) while the highest seed setting was recorded in Onion + Fennel (73.70 %) which was identical to Onion + Dill (70.50%) and Onion + Coriander( 72.37%) during 2011-12. In 2010-11, the highest seed yield (865.5 kg/ha) was obtained from Onion + fennel which was identical to Onion + coriander (838.1 kg/ha) but in 2011-12, the highest seed yield (1165.34 kg/ha) was recorded from Onion + fennel which was identical to Onion + coriander (1064.59 kg/ha). In both the years, percent seed setting was lowest in Sole onion (55.93 % in 2010-11and 57.73% in 2011-12). Accordingly, the lowest seed yield was also recorded from Sole onion (623.3 kg/ha in 2010-11 and 685.44 kg/ha in 2011-12). Dill and Fennel was the better attractant crop for pollination while coriander acted as intermediate. Int J Appl Sci Biotechnol, Vol 3(4): 737-743